THE ROLE OF SMES FUFU SKIPJACK PROCESSING TO MARINE INDUSTRY DEVELOPMENT IN BITUNG CITY NORTH SULAWESI - Jaclin I. Sumual; Yantje Uhing (Yayasan Education and Social Center, 2021)
The role of SMEs Fufu Skipjack Processing is crucial in improving the maritime industry in Indonesia, especially in Bitung City, North Sulawesi Province. There needs to be a deeper understanding of this role, particularly in terms of various factors such as the advantages, opportunities, disadvantages, and challenges that must be faced from the development of SMEs, especially in improving the maritime industry. This paper mainly examines the role of SMEs in the development of the marine industry in Bitung City with a study on SMEs in traditional fish processing. This study is in the form of a qualitative empirical study in direct interviews with entrepreneurs engaged in Fufu Skipjack processing. Data analysis is in the form of a SWOT analysis of this industry's strengths, weaknesses, opportunities, and threats. This study concludes that the SWOT analysis provides understanding and knowledge of various factors in the maritime industry development in Bitung City, especially the fish processing SMEs industry popular by people in Eastern Indonesia, namely Fufu Skipjack Processing